Isotopic evidence for the occurrence of biological nitrification and nitrogen deposition processing in forest canopies. (2nd November 2015) - Guerrieri, Rossella; Vanguelova, Elena I.; Michalski, Greg; Heaton, Timothy H. E.; Mencuccini, Maurizio
Abstract: This study examines the role of tree canopies in processing atmospheric nitrogen (Ndep ) for four forests in the United Kingdom subjected to different Ndep : Scots pine and beech stands under high Ndep (HN, 13–19 kg N ha −1 yr −1 ), compared to Scots pine and beech stands under low Ndep (LN, 9 kg N ha −1 yr −1 ). Changes of NO3 ‐N and NH4 ‐N concentrations in rainfall (RF) and throughfall (TF) together with a quadruple isotope approach, which combines δ 18 O, Δ 17 O and δ 15 N in NO3 − and δ 15 N in NH4 +, were used to assess N transformations by the canopies. Generally, HN sites showed higher NH4 ‐N and NO3 ‐N concentrations in RF compared to the LN sites. Similar values of δ 15 N‐NO3 − and δ 18 O in RF suggested similar source of atmospheric NO3 − (i.e. local traffic), while more positive values for δ 15 N‐NH4 + at HN compared to LN likely reflected the contribution of dry NHx deposition from intensive local farming. The isotopic signatures of the N‐forms changed after interacting with tree canopies. Indeed, 15 N‐enriched NH4 + in TF compared to RF at all sites suggested that canopies played an important role in buffering dry Ndep also at the low Ndep site. Using two independent methods, based on δ 18 O and Δ 17 O, we quantified for the first time the proportion of NO3 − in TF, which derived from nitrification occurring in tree canopies at the HN site. Specifically, for Scots pine, all the considered isotope approaches detected biological nitrification. By contrast for the beech, only using the mixing model with Δ 17 O, we were able to depict the occurrence of nitrification within canopies. Our study suggests that tree canopies play an active role in the N cycling within forest ecosystems. Processing of Ndep within canopies should not be neglected and needs further exploration, with the combination of multiple isotope tracers, with particular reference to Δ 17 O.